Implementation of Urban Farming with Fertigation System on Vegetable Commodities for Food-Independent Communities - Yuli Setiowati; Umar Battong; Asman Asman; Fiqri Jauhari Rizal; Mustofa Ali Rahman; Abdul Aziz Maulana (Universitas Lambung Mangkurat, 2024)
The objective of this community service action is to develop yards into plant cultivation areas with a fertigation system. Anticipated outcomes include the establishment of local food security within the community, which will promote a culture of food independence and protect the surrounding environment. This research was conducted from August to October 2023 through the utilization of the Participatory Rural Appraisal approach, lectures and demonstration plots. The outcome of this research is an enhancement in the partners' capacity to optimize the utilization of yards as cultivation areas for consumption crops, thereby realizing the long-term potential for achieving food independence. The researchers discovered that urban farming could be implemented in Tapis Village in order to establish a food-independent community. However, after receiving training, the researcher realized that for urban farming to be effective and increase community interest, it must also increase the economic value of the community.